Souvenir spoons : a comedy in one act / by Irving Dale. - Dale Irving. (Tufts University. Tisch Library., 2016)
1 online resource (11 pages).; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Series: Baker's edition of plays.